Use of viscosupplementation for the recovery of active football players complaining of knee pain [Corrigendum] - Migliore A; Giannini S; Bizzi E; Massafra U; Cassol M; Michael Abilius MJ; Boni G (Dove Medical Press, 2019)
Migliore A, Giannini S, Bizzi E, Massafra U, Cassol M, Abilius MJ, Boni G. Open Access Journal of Sports Medicine. 2019;10:11–15.Following publication, the authors of this article discovered an error on page 12, in Methods section, 3rd paragraph, 4th row regarding name and affiliation of hyaluronic acid applied in this study. Correct name and provenance is SINOVIAL 8 mg/mL (IBSA Farmaceutici, Italy).Read the original article